Role of infrared thermography in the assessment of burn wounds treated with and without hyperbaric oxygen therapy - Pradeoth Mukundan Korambayil; Prashanth Varkey Ambookan; Rameela Ravindran Karangath (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim is to study the role of infrared thermography in the assessment of burns wound treated with and without hyperbaric oxygen (HBO) therapy. Burn wound progression is assessed with clinical evaluation and infrared thermography for the patients subjected to HBO therapy with controls. Materials and Methods: This study was carried out in the plastic surgery department, from November 2018 to February 2019. A total of 21 patients with Burns were subjected to clinical evaluation and thermographic study. All patients were treated according to standard burns treatment protocol, and photographic data of clinical and thermographic imagings were sequentially recorded. These clinical and radiographic images were preserved for analysis. In 10 patients, HBO therapy was used as an adjunct for burns wound management and results were evaluated and rest of the patients was used as control. Results: Of 21 patients, with all patients' burns patients assessment done clinically and infrared thermography, 10 patients were subjected to hyperbaric therapy in random fashion and 11 patients were not subjected to HBO therapy. The duration of wound healing and wound progression to deeper planes were reduced in the patients subjected to hyperbaric therapy, which was evident both clinically and, by thermographic assessment. No complications were noted in patients subjected to HBO therapy. Conclusions: Infrared thermography can be used in association with clinical examination to assess the various types of burns wound and could be utilized for understanding the dynamic changes that happen in burns wound due to changes in the treatment protocol with evolving adjunct managements.